Evaluation of pregnancy diagnosis using ultrasonography in goats (Bangladesh Veterinarian, 2019)
Pregnancy status in 250 goats was determined by transabdominal ultrasonography. The registered hospital cases were divided into groups A (mated naturally; 88); B (postpartum reported unmated; 112) and C (pubertal unmated; 50). Animals found to be non-pregnant and free of uterine infection were labelled Group D and divided into synchronized (S) and control (NS) groups. GnRH followed byPGF2α nine days later was injected i.m. in group S, and NS group were allowed natural mating. All mated goats were checked monthly for pregnancy using ultrasonography. Pregnancy was diagnosed in 45.5, 4.5 and 0% from naturally mated, postpartum reported unmated and pubertal unmated cases, respectively. The oestrus detection and pregnancy rates varied significantly (P